2022
DOI: 10.3390/socsci11030096
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Parental Control in Early Childhood in the Context of U.S. Latino Families in the 21st Century

Abstract: This review focuses on the role of parental control in the sociocultural context of U.S. Latino families with young children in the 21st century. The review begins with a historical overview of the concept of parental control and a summary of theoretical approaches to the study of parenting in context. Associations between different forms of parental control and children’s adjustment are summarized, with special attention to cultural considerations and the role of maternal warmth in research involving Latino f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…Thus, it did not appear that parental warmth significantly moderated the impact of intrusive parenting in Latinx DLL families. This contrasts with prior studies finding parental warmth to be a critical moderator of this relationship in certain samples (Benito-Gomez, 2020). Given that our sample is specially DLLs within the Latinx community, it is possible that these factors relate differently in our sample compared to others.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, it did not appear that parental warmth significantly moderated the impact of intrusive parenting in Latinx DLL families. This contrasts with prior studies finding parental warmth to be a critical moderator of this relationship in certain samples (Benito-Gomez, 2020). Given that our sample is specially DLLs within the Latinx community, it is possible that these factors relate differently in our sample compared to others.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, prior examinations in different Latinx samples have found parental warmth may be an additional moderator, such that intrusiveness is only neutral or beneficial when it is also practiced with high levels of warmth. In a study of Latinx toddlers, Benito-Gomez (2020) found that parental intrusiveness was only related to increased behavior problems in children whose mothers displayed low levels of warmth.…”
Section: Family Factors Influencing Social Emotional Development In Dllsmentioning
confidence: 99%
“…Among Hispanic/Latino families, however, findings have been more mixed, with studies finding negative, nonexistent, or positive influences of intrusiveness on certain child markers, depending on important moderators such as acculturation (Ispa et al, 2004; Yomtov et al, 2015). In a recent study of this parenting dimension, Benito-Gomez (2020) examined how intrusiveness related to internalizing and externalizing behavior problems in Hispanic/Latino children at ages 14 and 24 months, as well as how parental warmth moderated this relation. She found that parental intrusiveness was only related to increased externalizing in children whose mothers displayed low levels of warmth.…”
Section: Intrusiveness In the Context Of Race/ethnicitymentioning
confidence: 99%